Software bugs management (ISO/IEC/IEEE 29119 standard) system - Chin, Jun Kang (2020)
Bug management is a crucial process in the software development process. Low-quality bug management could result in low-quality deliverable, resources wasted and profit lost. However, bug management is not an easy process, software developers often have a hard time managing software bugs. This is because a development team involves not only technical software developer but also non-technical business unit. It can be hard to communicate between the development team as the members have a different level of technical knowledge. To solve this problem, this project proposes a bug management system as a solution. Although there are many existing bug management systems, most of them do not provide a standardized bug management process. The proposed system provides a standardized bug management process following the ISO/IEC/IEEE 29119 Software Testing Standard. The proposed system also aims to improve the understanding of the software bugs and improve the communication between the development team. With the help of the proposed system, the software developer can focus on the software developing and software development team including business unit can communicate more effectively.